Effect of Brassicaceae Waste Application on Soil Nematode Community - Ibrahim, Ahmad Yusuf; Supramana, Supramana; Giyanto, Giyanto (Universitas Gadjah Mada, 2022)
Brassicaceae are known to contain compounds that are biofumigants. This study aimed to determine the effect of Brassicaceae waste application on soil nematode community. Broccoli leaves and stems (Brassica oleracea var. italic), cabbage leaves and stems (B. oleracea var. capitate), kailan stems (B. oleracea var. alboglabra), radish leaves (Raphanus sativus), and leaves of kamanilan weed (Rorippa indica) were tested in this study. The total glucosinolate content of Brassicaceae waste was estimated using the palladium method with a modified spectrophotometer. The experiment was carried out in polybags containing 500 grams of soil-infested nematodes. Brassicaceae waste (15 grams/polybag) was chopped and mixed into the soil, watered, and polybags were tightly closed for 14 days. The experiment was arranged in a completely randomized design with nine treatments and five replications. The results of the total glucosinolate analysis showed that broccoli, radish, and kamanilan leaves fall into the high category (144.7-185.2 µmol/g); cabbage leaves, cabbage stems, and kailan stems fall into the medium category (52.0-56.0 µmol/g); and broccoli stems fall into the low category (35.4 µmol/g). There was no correlation between total glucosinolate contents and their effect on suppressing soil nematode communities at the applied effluent dose. The population of bacterivorous nematodes increased in each waste treatment, especially in kamanilan leaf treatment (R. indica) which reached 13,008 individuals. These results indicate that kamanilan weed has good potential to improve soil health. The treatment of Brassicaceae waste against soil nematode communities showed a low diversity index, an uneven evenness index, and a high dominance index.